Dijital Ortamda Marka İletişimi: Tekstil Sektöründe Moda Bloglarının Tüketici Üzerindeki Etkisi - Yengin - Ataman, Didem; Sağıroğlu, Yakup (The Turkish Online Journal of Design, Art and Communication, 2012)
Information and communication technologies are developing and changing with each passing day. All these changes have a great impact on society's life style. With the ripple effect of internet usage people get advantages about money and time saving. Therefore, individuals take a place on digital media. On the other hand, brands aware of this change and tend to blogs. This is an effective way for brands to liaise with their customer base. They can inform their customers about specific products and business community. Also, blogs are forcible about networking to increase their sales. Furthermore, many people will be heaped together by digital media.Therefore, this exposes to get different ideas and digital media merge into "a digital commumication society". Besides these, it has an important effects for brands to create customer loyalty and customer sense .Customers can think and commit their thoughts to writing. Consequently, this is a supportive way for managements to influence their customers. İn this context, survey will be applied on sample group to analyze fashion blogs' effects on their customers. Research results will be apprised on the basis of " brand loyalty".
Keywords: Brand Communication; Digiital Media; Bloges; Consumer; Shopping; Marka İletişimi; Ortam Dijiital; Tüketici; Alışveriş